2022
DOI: 10.1002/ajh.26586
|View full text |Cite
|
Sign up to set email alerts
|

A novel adoptive synthetic TCR and antigen receptor (STAR) T‐Cell therapy for B‐Cell acute lymphoblastic leukemia

Abstract: We developed a T-cell-receptor (TCR) complex-based chimeric antigen receptor (CAR) named Synthetic TCR and Antigen Receptor (STAR). Here, we report preclinical and phase I clinical trial data (NCT03953599) of this T-cell therapy for refractory and relapsed (R/R) B-cell acute lymphoblastic leukemia (B-ALL) patients. STAR consists of two protein modules each containing an antibody light or heavy chain variable region and TCR α or β chain constant region fused to the co-stimulatory domain of OX40. T-cells were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…1 H ), recapitulating the observation in patient #0 and rendering the KS culture a suitable system for further mechanistic investigations. To generalize the observation to conventional CD19-targeting CAR T, we generated KS by killing Raji B cells with previously described BBz-CAR T cells ( Wang et al, 2022 ). Consistently, both prophylactic and conditional metoprolol treatment impaired BBz-KS–induced IL-6 protein production in human monocytes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 H ), recapitulating the observation in patient #0 and rendering the KS culture a suitable system for further mechanistic investigations. To generalize the observation to conventional CD19-targeting CAR T, we generated KS by killing Raji B cells with previously described BBz-CAR T cells ( Wang et al, 2022 ). Consistently, both prophylactic and conditional metoprolol treatment impaired BBz-KS–induced IL-6 protein production in human monocytes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…BBz-CAR was generated as previously described ( Wang et al, 2022 ). Briefly, the sequences of FMC63 scFv, the CD8 transmembrane domain, and CD3ζ plus 4-1BB signaling chains constituted the CD19 + CAR construct.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that although third-generation CARs' in vivo persistence was generally improved in preclinical mouse xenograft models of pancreatic cancer, the anti-tumor potency of the secondgeneration CARs still outperformed the third-generation formats [81]. In a different study, third-generation anti-GD2 CARs with CD28-OX40-CD3ζ domains produced better in vitro cytokine secretion (IL-2, TNFα) and proliferation than second-generation (CD28-CD3ζ or OX40-CD3ζ) and firstgeneration (CD3ζ) forms [82]. Apart from structural variations in co-stimulatory domains, patient heterogeneity and different therapies may potentially contribute to the dearth of advantages of third-generation CARs.…”
Section: Second Generation Car-t Cells Havementioning
confidence: 98%
“…Moreover, mutSTAT co-stimulated with OX40 significantly prolongs the in vivo persistence. CD19 specific mutSTAR-OX40 has been found to have a 100% CR rate in treating 18 patients with r/r B-ALL 4 weeks post infusion in a phase I clinical trial: 75% (12/16) patients remained leukemia-free after a median follow-up of 545 (433-665) days; 55.6% patients (10/18) had mild CRS; and two patients had grade III neurotoxicity [206]. In another preclinical study, V L and V H domain of the Fab of human anti-CD19 (ET190L1, clone) were fused with the δ chain and γ chain of TCR respectively to direct CD19 antigen specificity and antigen dependent CD3γε/CD3δε/ CD3ζζ signaling, cytokine production, degranulation.…”
Section: Hematology and Oncology Discoverymentioning
confidence: 99%